EFEKTIVITAS PELAKSANAAN KEBIJAKAN DANA DEKONSENTRASI TERHADAP PENINGKATAN KUALITAS LINGKUNGAN HIDUP - Meidiza Dwi Orchidea; Sri Mulatsih; Yeti Lis Purnamadewi (Graduate School Bogor Agricultural University (SPs IPB), 2016)
One of the mechanisms for encouraging local governments to achieve national priority targets for environmental sector is through allocating the deconcentration budget of environment for the provincial. According to Government Regulation No. 7/2008, the deconcentration budget allocation for the region should be in accordance with finance minister recommendation indicators and environmental indicators. However, the allocation of deconcentration budget of environment is not yet consider those indicators. So that, the allocation of deconcentration budget has been constantly increasing, on the other hand the quality of environment has been decreasing. Therefore, the aims of this research are to analyze the factors that influence the allocation of deconcentration budget of environment in province and to analyze the effectiveness of deconcentration budget in order to improve environmental quality in Indonesia. This study uses panel data, with cross section data of 32 provinces in the period of 2009 to 2013. The research methods are descriptive analysis and analysis of panel data. The results indicated that indicators of fiscal capacity, numbers of industry, sizes of land cover, and numbers of complaints on environmental case have a significant effect on the allocation of deconcentration budget. Results also showed that deconcentration budget has influenced the environmental quality improvement.